Analisis Perbedaan Kecenderungan Pemaafan dan Dendam pada Remaja di Makassar - Firdaus, Faradillah (Indonesian Journal of Social and Educational Studies, 2024)
Abstract. This study aims to determine the tendency differences between forgiveness and revenge among adolescents in Makassar. This research method is quantitative and the data analysis technique is regression analysis tested using SPSS 26. The number of participants in the study was 200 adolescents who were taken using simple random sampling technique. The measuring instrument used is the Likert scale for forgiveness and revenge. The results showed that there was a weak positive correlation (r = 0.1153) between forgiveness and revenge tendencies, with only 1.33% variance explained by the model. The weak positive relationship between resentment and forgiveness suggests that these two constructs may be more independent than previously assumed. These results support Worthington's (2006) view that the forgiveness process involves a variety of complex factors, not only related to a person's level of resentment. Keywords: forgiveness, revenge, adolescent, correlation